ANALISIS KEBERLANJUTAN USAHATANI UBI KAYU (MANIHOT UTILISSIMA) SECARA MULTIDIMENSI DAN PARSIAL DI KABUPATEN WONOGIRI - Febriani Puspitaningrum; Endang Siti Rahayu; Erlyna Wida Riptanti (Jurnal Dinamika Sosial Ekonomi, 2024)
Cassava is a tuberous food commodity that has the potential to encourage the development of the country's economy. Wonogiri Regency is the region with the largest cassava production level in Central Java Province, but productivity and harvest area fluctuate and even tend to decline. This decline in productivity can disrupt the availability of cassava and lead to the unsustainability of cassava farming in Wonogiri Regency. Therefore, research on the sustainability of cassava farming in Wonogiri Regency needs to be conducted. The research was conducted in Ngadirojo, Tirtomoyo, and Pracimantoro sub-districts by taking a sample of 70 farmers. The method used in this study was Multidimensional Scaling (MDS). The results of the analysis show that multidimensionally cassava farming in Wonogiri Regency is less sustainable. Partially, the ecological, economic and technological dimensions are less sustainable, while the social dimension has a fairly sustainable status. Further analysis was conducted to determine the sensitive attributes that affect the sustainability status of each dimension. The most sensitive attribute in the ecological dimension is the availability of water during the planting period, the economic dimension is marketed crop yields, the technological dimension is the use of seeds from previous harvests, and the social dimension is conflict in farming.